2017
DOI: 10.1371/journal.pone.0180125
|View full text |Cite
|
Sign up to set email alerts
|

Body weight concerns: Cross-national study and identification of factors related to eating disorders

Abstract: BackgroundBody weight concerns are common among individuals with eating disorders, and this construct can be assessed using psychometric instruments. The Weight Concerns Scale (WCS) is commonly used to assess body weight concerns.AimsTo evaluate the psychometric properties of the WCS with Brazilian, Portuguese, and Mozambican female college students; to estimate body weight concerns; and to identify factors related to eating disorders.MethodsConfirmatory factor analysis was performed. Factorial, convergent, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
2
20
0
6
Order By: Relevance
“…36,37 This finding highlights the relevant role that eating can play in an individuals' body appearance. The significant paths between economic class and body image have been reported in previous studies, 17 illustrating how individuals with greater economic power are more dissatisfied with their body and may engage more often in strategies to seek body change. 38 No prior study has reported results similar to ours in relation to the significant paths found between work and strategies for body change.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…36,37 This finding highlights the relevant role that eating can play in an individuals' body appearance. The significant paths between economic class and body image have been reported in previous studies, 17 illustrating how individuals with greater economic power are more dissatisfied with their body and may engage more often in strategies to seek body change. 38 No prior study has reported results similar to ours in relation to the significant paths found between work and strategies for body change.…”
Section: Resultsmentioning
confidence: 53%
“…Another point that merits highlighting is related to evaluation of the psychometric properties of BIBCI, which is rarely reported in the literature, and the related lack of consensus among researchers on the analytical strategy for estimating BIBCI subscale scores (i.e., some studies use means, and others use sums). The authors of the BIBCI did not In previous studies, 11,[14][15][16][17] Analyses were carried out using MPLUS (v.7.2). Average variance extracted (AVE) was calculated to evaluate convergent validity.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors report, for example, that women wish mainly to lose weight, while men seek weight gain in the form of muscle mass (Adami et al, 2008;Demarest & Allen, 2000;Muth & Cash, 1997;Nikniaz et al, 2016;Radwan et al, 2019). These studies also point out that women have a higher negative body image when compared to men and this may contribute to the development of harmful behaviors, such as disordered eating (Da Silva et al, 2020, Silva et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…E a pouca literatura encontrada é controversa, pois alguns autores afirmam que os comportamentos sugestivos de TA estão mais associados a indivíduos das classes média e alta, outros os associam com a classe baixa e, ainda, outros dizem que essa associação não é totalmente correta, havendo pouco ou nenhum efeito da classe social. Os autores concluem que essa relação ainda precisa ser mais estudada [5][6][7] .…”
Section: Introductionunclassified